Reflections of the global implementation of intellectual property rights on pharmaceutical policies: the case of Turkey - Doğan, Nazlı Bülay. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2012., 2012)
This thesis examines how the pharmaceutical policies are affected by the global implementation of intellectual property rights (IPRs) in the era of neoliberal globalization and, in return, how these policies affect the pharmaceutical sector and multinational pharmaceutical companies (MPCs), which are the main actors of this implementation process. For this objective, the study is organized in three chapters where first, the global implementation of IPRs is examined; second, the pharmaceutical policies affected by this implementation are discussed and last, their reflections in Turkey are explored. During the thesis, the literature reviews on IPRs and pharmaceutical policies are reinforced with the examination of sector reports, media scans, press releases and interviews for the aim of studying this dynamic political process. In the particular case of Turkey, the current situation is the result of a long process going back to the 1960s, since when the interests of different actors are facing each other. It is undeniable that the global implementation of IPRs creates a favorable atmosphere for MPCs, affects the domestic sector negatively, and results in increasing public pharmaceutical expenditures. For that reason, the Turkish government has conducted cost containment policies aimed especially at these drugs in question, relying on its monospony position. However, according to another result, there has not yet been a violent confrontation between MPCs and the Turkish government. Moreover, there is a tendency to loosen the tension between them. For that reason, it is believed that the current political situation will be unbalanced in the near future.
Keywords: Pharmaceutical industry -- Turkey.; Intellectual property (International law).